PHARMACOEPIDEMIOLOGY OF CARBAPENEMS APPLICATION AMONG THE PREMATURE NEWBORNS IN SAINT PETERSBURG. WORLD EXPERIENCE IN NEONATOLOGY - A.S. Kolbin; A.B. Ivanyuk; V.A. Lyubimenko; N.P. Shabalov (Union of pediatricians of Russia, 2008)
Premature newborns are a high risk group in terms of the infection complications growth. therefore, it is highly urgent to choose the efficient and safe antibacterial medications for the given category of patients. The authors carried out a pharma coepidemiological study of the carbapenems application among 353 newborns with very low body weight at birth, as well as the literature analysis on the use of this medications group in compliance with the evidence based medicine. As a result, they showed that for the last 8 years the frequency of the carbapenems application in Saint-Petersburg among the newborns has grown from 10 to 52%. It is statistically accurate that imipenem/cilastatin was more often used to the amount of 25 mg/kg twice a day. In 71% of cases, carbapenems were applied in the form of the empiric therapy against the general bacterial infection in combination with vancomycin and/or metronidazole. Antibiotics proved to be safe. The literature analysis showed that there is no data, which would allow one to compare the efficiency of carbapenems with other antibiotics among the newborns based on the results of the meta analyses and randomized clinical studies. Nowadays, carbapenems demonstrated high efficiency and safety in the small clinical observations.Key words: carbapenems, imipenem, meropenem, newborns with very low body weight at birth.